The impact of childhood trauma on intimacy: A literature review exploring Drama Therapy techniques for intimacy recovery in adult relationships. - Magee, Kathryn (University of the Witwatersrand, Johannesburg, 2023)
This research paper explores how Drama Therapy techniques may be used for intimacy recovery in adult relationships in the context of childhood trauma. The immediate and long term consequences of childhood trauma are multifaceted and vary significantly. However, studies indicate that exposure to trauma during childhood adversely impacts brain development, which may disrupt other developmental processes as well as an individual’s capacity to form and maintain intimate relationships in adulthood. Intimacy is a vital element of relationships in that it provides a framework for communication and connection on various levels. Despite correlations between the two notions, research pertaining to the treatment of trauma with the intention of fostering intimacy is limited. Similarly, in the Drama Therapy field, there is little evidence indicating how the discipline could be adapted with the specific intention of fostering intimacy in relationships. Through an integrative literature review method, research pertaining to the impacts of childhood trauma, how childhood trauma influences intimacy, and predominant trauma treatment approaches and their effects, were explored. This informed an analysis of various Drama Therapy approaches, which may be useful in dealing with childhood trauma and fostering healthy relationships. From the literature examined, Drama Therapy may serve as a versatile tool for emotional regulation, narrative exploration, vulnerability and sharing, and transformation and empowerment, which all have the potential to foster intimacy in relationships
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in the field of Drama Therapy to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2024
Keywords: Drama Therapy; Childhood trauma; Intimacy; Relationships; Trauma Treatment; SDG-3: Good health and well-being